2021
DOI: 10.1039/d0en00974a
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the interactions between nano-hydroxyapatite and the roots of phosphorus deficient barley plants

Abstract: The recent introduction of nanotechnology in plant science has paved the way for the development of more efficient fertilizers. However, progress in research is currently hampered by a poor understanding...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…LA-ICP-MS was employed to analyze the distribution patterns of As, Si, and S in node I, since it has been proved to be a powerful approach for multi-elemental imaging at the cellular level in rice nodes. 36–38 The results obtained will provide a better understanding of the regulation mechanisms of As transport from nodes to grains by foliar application of silica NPs, which will be helpful to guide its application on rice grown in As-contaminated paddy fields to ensure grain safety.…”
Section: Introductionmentioning
confidence: 99%
“…LA-ICP-MS was employed to analyze the distribution patterns of As, Si, and S in node I, since it has been proved to be a powerful approach for multi-elemental imaging at the cellular level in rice nodes. 36–38 The results obtained will provide a better understanding of the regulation mechanisms of As transport from nodes to grains by foliar application of silica NPs, which will be helpful to guide its application on rice grown in As-contaminated paddy fields to ensure grain safety.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Moreover, the high capability to be doped with foreign ions or molecules (e.g., K + , Mg 2+ , Zn 2+ , CO 3 2-, NO 3 -, urea, etc), and tuneable solubility make them as the ideal nanoplatform to provide a sustained delivery of multinutrients upon nanoparticle dissolution. [29][30][31] In fact, several works in agrochemical field demonstrated the potential of ACP and Ap nanoparticles for the controlled delivery of plant macronutrients, such as phosphorous [32][33][34][35][36][37][38] and nitrogen. 29,30,[39][40][41][42] Synthetic Ap nanoparticles have been also functionalized with humic subtances (HS) providing the synergistic co-release of crop nutrients and stimulants.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, it has been demonstrated that citratestabilized nHAP and nano-RP provided P to barley plants in a hydroponic system, and nHAPs were shown to be taken up by the roots of the plant. 30 In our previous studies, we have demonstrated that P-based NMs have no inhibitory effect or toxicity to different plant growth-promoting rhizobacteria (PGPR) over a broad concentration range (∼1−1000 mg•mL −1 ), suggesting their safety on beneficial soil PGPR strains. 8 Further, these P-based NMs were also found to be non-toxic to soil-dwelling nematodes, Caenorhabditis elegans, 31 and zebrafish embryos.…”
Section: Introductionmentioning
confidence: 99%
“…These NMs have been used as fertilizers mainly via the foliar application, and very little is known about the application of NMs using the fertigation approach in soil and their uptake in the plant systems. Very recently, it has been demonstrated that citrate-stabilized nHAP and nano-RP provided P to barley plants in a hydroponic system, and nHAPs were shown to be taken up by the roots of the plant …”
Section: Introductionmentioning
confidence: 99%